El caballo negro : el quinto caso del sheriff Walt Longmire - Johnson, Craig, 1961- (Nuevos tiempos (Madrid, Spain), 2016)
In the sparse and rugged landscape of Wyoming, sheriff Walt Longmire goes undercover to save a woman accused of killing her husband.